Social Support and Satisfaction with Life in Families with Low Financial Status Raising a Child with ASD During the Pandemic Covid-19 - Anna Gagat-Matuła (Communications of International Proceedings, 2021)
The outbreak of the pandemic Covid-19 caused significant changes in various areas of daily life. Due to the introduced restrictions, people with disabilities and their families, who lost the possibility of obtaining social support adequate to their needs, found themselves in a particularly difficult situation. People with autism spectrum disorders, who have significant problems with accepting change, have had to face new conditions of life during the pandemic. The purpose of the article is to define the nature of the relationship between satisfaction with life in the surveyed families with low financial status, raising an child with ASD and the social support received during the pandemic Covid-19. Correlation analysis showed significant positive relationships between received social support and the satisfaction with life of the study subjects. The empirical analysis shows that for families with low financial status raising a child with ASD, it is important to receive social support from relatives, parents, a spouse and psychologists / therapists, as they support them in fulfilling their responsibilities related to raising a child with ASD. The importance of social contacts for the studied families is also confirmed by the relationships identified between satisfaction with life and the support received from people in the respondents’ closest environment: friends and neighbours.
Keywords: Material situation; autism; satisfaction with life; social support; pandemic Covid-19